1992
DOI: 10.1111/j.1365-2303.1992.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Staining of Serous Effusions With the Monoclonal Antibody Ber‐Ep4

Abstract: Cytospin preparations were made from 102 serous effusions for immunocytochemical staining using a panel of monoclonal antibodies including a new monoclonal antibody Ber-EP4. On cytological examination, 32 fluids were reported to contain tumour cells consistent with metastatic adenocarcinoma; 66 contained benign cells only and three were reported to contain cells suspicious of malignancy. One effusion contained tumour cells consistent with malignant mesothelioma. Positive staining of the tumour cells with Ber-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 12 publications
3
32
0
1
Order By: Relevance
“…This is in line with previous studies which generally have reported a factor of two-to threefold over conventional cytology for tumour cell detection in effusions (Johnston et al, 1987;Lidang Jensen and Johansen, 1994). Among the various antibodies which have been used, Ber-Ep4 (Latza et al, 1990) has shown itself to be highly reliable for the detection of epithelial tumour cells, with a sensitivity of 83Ð100%, a positive predictive value of 96%, and a false-positive rate of 2Ð7% (De Angelis et al, 1992;Stoop et al, 1992;DiazArias et al, 1993;Robinson and Royston, 1993;Lidang Jensen and Johansen, 1994). Juhl et al (1994) and Broll et al (1996) were among the first to report results with immunocytology in peritoneal lavage specimens for a variety of gastrointestinal carcinomas.…”
Section: Fptc: Immunocytologysupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with previous studies which generally have reported a factor of two-to threefold over conventional cytology for tumour cell detection in effusions (Johnston et al, 1987;Lidang Jensen and Johansen, 1994). Among the various antibodies which have been used, Ber-Ep4 (Latza et al, 1990) has shown itself to be highly reliable for the detection of epithelial tumour cells, with a sensitivity of 83Ð100%, a positive predictive value of 96%, and a false-positive rate of 2Ð7% (De Angelis et al, 1992;Stoop et al, 1992;DiazArias et al, 1993;Robinson and Royston, 1993;Lidang Jensen and Johansen, 1994). Juhl et al (1994) and Broll et al (1996) were among the first to report results with immunocytology in peritoneal lavage specimens for a variety of gastrointestinal carcinomas.…”
Section: Fptc: Immunocytologysupporting
confidence: 89%
“…Specifically, very high degrees of sensitivity and specificity can be achieved using the antibody Ber-Ep4 (Latza et al, 1990;De Angelis et al, 1992;Stoop et al, 1992;Diaz-Arias et al, 1993;Robinson and Royston, 1993). This antibody recognizes epithelial glycoproteins 34 and 49 kDa in size, found on the epithelial cell membrane, which correspond to nidogen, a matrix adhesion protein (Simon et al, 1990).…”
mentioning
confidence: 99%
“…Several antibodies to EGP-2 cell-surface protein have been described, but the most widely utilized is the monoclonal antibody Ber-EP4 (Latza et al, 1990). Ber-EP4 immunostaining has been used for the identification of carcinomatous effusions (Sheibani et al, 1991;de Angelis et al, 1992;Illingworth et al, 1994;Maguire et al, 1994).…”
mentioning
confidence: 99%
“…De Angelis et al (2) applied Ber-EP4 to serous effusions. The results show that Ber-EP4 stained 100% of metastatic adenocarcinoma but did not stain mesothelial cells.…”
Section: Discussionmentioning
confidence: 99%